2009
DOI: 10.2746/042516409x391042
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of the superficial digital flexor tendons of National Hunt racehorses in training over two racing seasons

Abstract: Variation in the prevalence of tendinopathy between yards suggests that training methods may influence injury rate. It was not possible to predict injury using routine ultrasonography and therefore other methods must be identified. A normal reference range for SDFT CSA is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 20 publications
1
76
0
1
Order By: Relevance
“…In humans, the prevalence of Achilles injury is reported as 3% in the general population under 45 years of age [22], increasing to 15-56% in elite athletes, depending on the type of sport undertaken [22,23]. Injury to the SDFT in athletic horses is also common, with SDFT pathology reported in 11-24% of thoroughbred racehorses [24,25] and shows a similar initiation and progression to human Achilles tendinopathy [26,27]. Further, tendons become more prone to injury with increasing age, with regards to both the human Achilles [22,28] and equine SDFT [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the prevalence of Achilles injury is reported as 3% in the general population under 45 years of age [22], increasing to 15-56% in elite athletes, depending on the type of sport undertaken [22,23]. Injury to the SDFT in athletic horses is also common, with SDFT pathology reported in 11-24% of thoroughbred racehorses [24,25] and shows a similar initiation and progression to human Achilles tendinopathy [26,27]. Further, tendons become more prone to injury with increasing age, with regards to both the human Achilles [22,28] and equine SDFT [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] During maximal exercise, the SDFT operates close to its biomechanical limits. 5 Injury can result following an accumulation of microdamage, age-induced degeneration, damage caused by repetitive cycling, or a single acute overload.…”
mentioning
confidence: 99%
“…Future studies preferably should include scintigraphic follow-up of youngsters in training to evaluate the effect of certain training schemes on bone metabolism. Follow-up investigation of tendon remodeling is a more diffi cult issue, as a recent study showed that developing core lesions could not be depicted by ultrasonography in the early phase (Avella et al 2009 ), and when visible, an acute tendon injury was likely to occur. Standing MRI is a potential alternative but at the moment limited due to availability and costs.…”
Section: Resultsmentioning
confidence: 99%